Addressing The Hurdles: Enhancing Better Policies In Indonesia Cyber Security Management Amidst Uncertainty - Imran, Mohammad Fadil; Gunawan, Hendra; Asmoro, Dwi (Universitas Padjadjaran, 2024)
The purpose of this study is to address obstacles to cyber security in Indonesia. Using a systematic literature review (SLR) based on Scopus and Google Scholar, this study identifies tangible obstacles such as infrastructure-related, low preparedness for digitalization, and scarcity of skilled personnel. Intangible issues such as legal frameworks and regulatory vacuums and neglect of cyber security in smart cities are also noted. To address these issues, this study suggests a number of policy recommendations for the Indonesian government, including investments in cyber security development, creation of a cyber security maturity model, enhancement of human resource capabilities, role clarification, improved legislation, and promotion of collaborative security management. If followed, these suggestions have the potential to strengthen Indonesia’s cyber security defenses considerably and provide a safer digital environment for its residents and enterprises.